(untitled) (Journal of Governance and Development (JGD), 2020)
Secrecy in government is almost always perceived as being antithetical to accountability and transparency in the conduct of democratic government. However, it is undisputable that government secrecy is practiced the world over because it is indispensable to state security, international relations, public and personal interests. Hence, democratic governments must perform a delicate balancing act between openness and confidentiality in the handling of official information. Indeed, effective governance requires various legal regimes that control government information through security classifications and impose punishments on offenders. This paper aims to address the dearth of research on government secrecy and security classifications in the context of integrity management in Malaysia. Integrity management encompasses not only the exercise of moral values by public institutions and officials but also the integrity of processes and procedures that uphold the integrity of governance. This exploratory research uses qualitative content analysis of data gathered from official government publications and websites, relevant documents and course notes, as well as interviews and correspondence with field experts. The inferences derived from themes and categories generated have resulted in several important findings. First, the 1972 Official Secrets Act (OSA) plays a significant role as part of a plethora of statutes and ethical codes that are indispensable to upholding government integrity. Second, weaknesses in balancing between openness and confidentiality when handling official information are attributed to organizational failure, public officials’ lack of ethical values, comprehension and training. The challenge is to ensure that the OSA is not used for cover-ups of corruption, ethical misconducts and administrative transgressions while the proposed Freedom of Information Act does not lead to a culture of blaming and mistrust that could lead to the paralysis of government and governance.